Development of the Serayu Network Social Innovation as An Effort to Preserve the Sustainability of the Serayu Watershed Ecosystem - Budiarto, Condro; Utami, Matahun Triastuti Budi; Fansyah, Maman (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
Banjarnegara Regency, as an agrarian region, is highly dependent on the sustainability of the Serayu Watershed ecosystem. However, land use changes in the upstream area have triggered environmental degradation in the form of erosion, sedimentation of the Mrica Reservoir, and a decline in water quality, all of which impact the community’s economic vulnerability. In response to these issues, PT PLN Indonesia Power UBP Mrica initiated the Serayu Network Program as a social innovation that integrates environmental conservation with the strengthening of the local economy. Through six stages of social innovation, the program was systematically developed with a sustainability orientation, implemented through integrated farming in the Kampung Ilmu Serayu Network as well as the empowerment of vulnerable groups through vocational training. The program’s outcomes demonstrate multidimensional impacts, including the restoration of the watershed's ecological functions, increased community income, business diversification, and innovations based on the circular economy. Therefore, the Serayu Network serves not only as a model of local empowerment but also as a representation of social innovation with the potential to be replicated in other watersheds in Indonesia as an effort to build sustainable socio-economic and ecological resilience.